Optimal Configuration of Fire-Storage Capacity Considering Dynamic Charge-Discharge Efficiency of Hybrid Energy Storage - Huang , Hongbo; Wang, Hui; Cai, Yang; Chen, Xiwei; Li, Tingting (Frontiers in Energy Research, 2022)
The combination of thermal power and hybrid energy storage is an effective way to improve the response ability of Automatic Generation Control (AGC) command in thermal power plants. Notably, the configuration of hybrid energy storage capacity is directly related to the improvement of frequency modulation ability of thermal power plants and the coordination of economic benefits. However, the constant efficiency model adopted in capacity configuration will misjudge the actual operating status of each energy storage unit, resulting in unreasonable capacity allocation. In this context, a fire-storage capacity optimization configuration model considering dynamic charge-discharge efficiency of hybrid energy storage is established. The model presents the functional relationship between charge and discharge power and efficiency of different types of energy storage. Simulation proves that the proposed strategy can meet the tracking demand of ACE signal in thermal power plants and reduce the planning and operation cost of energy storage.